The Composition of Purse seine During The Morning and at Afternoon in The Sasak Jorong Pasa Lamo Ranah Pasiesie, District West Pasaman, West Sumatera Province - Rengi, Pareng; ', Hendri; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractThis research was conducted on Juni 23th 2014, in the Sasak Jorong Pasa Lamo Ranah Pasisie, District West Pasaman, West Sumatera Province. The purpose of this study was to determine the differences in the composition of purse seine during the morning and at afternoon.This research used a survey method. The operation of purse seine fishing gear held on over 5 days.The Purse seine catches consist of 7 species, either in the morning or at aafternoon with the weight was 692 kg at noon (1,748 fishes) and at afternoon was 589 kg (1,484 fishes), overall the weight were 1281 kg (3,232 fishes). The species of fish which were caught consist of Acanthocybium solandri, Auxis thazard, Stromsteus niger, Selaroides leptolepis, Caranax melampygus, Leioghnathus equulus, Rastrelliger faughni.T-test and Chi-square test showed that there is differences in the average and composition of catches during the morning and at afternoon.Keyword: Purse seine, the morning, at afternoon, West sumatera.